Epidemiology and Clinical Characteristics of Urogenital Tuberculosis in Sabah, Malaysia - Karthikayenee Ramasamy; Shankaran Thevarajah (Société Internationale d’Urologie Journal)
ObjectivesWe aimed to describe the epidemiology and clinical characteristics of urogenital tuberculosis (UGTB) in Sabah, Malaysia. MethodsWe performed a retrospective, descriptive study based on medical records of UGTB cases identified between January 1, 2014, and November 30, 2020. ResultsWe identified 131 cases of UGTB in Sabah. Patient gender was balanced except for a mild male predominance in the 35 to 44 age group. No cases were reported in children. The majority of the patients (96%) were diagnosed in the government facility. Among the UGTB cases, 72% of patients were from rural areas, and 29% were illiterate. The commonest presentation was frequency of micturition (28%), followed by abdominal pain (26%) and loss of appetite (26%). The common sites included renal (32%) and scrotal (25%). Diagnosis was achieved via histopathology in 39.7% of patients and smear microscopy in 35.9%. Anti-tubercular treatment duration was 8.6 (±SD 4.0) months, and 81% of patients have completed treatment. A total of 50.4% of patients had received surgical intervention; 10.7% had undergone incision and drainage, 9.9% had cystoscopy, and 6.9% underwent orchidectomy. ConclusionUGTB has varied non-specific symptoms, which poses a diagnostic challenge, leading to morbidity. Ensuring awareness via widespread education within government and private health care, along with rural outreach programs, will contribute to early recognition and treatment.